Finfish aquaculture diversification - Le Francois, Nathalie R. (CABI, 2010)
Offers information on the biology, domestication and aquacultural characteristics of a wide selection of fish species. This book presents a rationale of species diversification, different approaches to species selection and the basic economical and market considerations governing the launch of strategic development and commercialization efforts